The Notary's Responsibility for Legalization of Letters Underhand Based on Basic Legal Values - Octaviani, Sri Ayuning Triana Rizqi; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research aims to determine and analyze the responsibility of Notaries for the legalization of private documents based on basic legal values and the legal consequences of private letters that have received Notarial legalization. The approach that this author will take is the Sociological Juridical approach. The Sociological Juridical Approach emphasizes research that aims to obtain legal knowledge empirically by going directly into the object. Sociological Juridical Research is legal research using secondary data as initial data, which is then continued with primary data in the field or towards the community, examining the effectiveness of a Ministerial Regulation and research that seeks to find relationships (correlations) between various symptoms or variables. Based on research, it can be concluded that the Notary's responsibility for the veracity of the legalized private letter is the certainty of the signature, meaning that it is certain that the person signing the signature is indeed the party in the private letter, not someone else. The legal consequences of a private letter that has received legalization from a Notary can be more helpful for the judge in terms of proof because by acknowledging the signature, the contents of the letter are considered to be an agreement between the parties because the truth of a private letter lies in the signatures of the parties, so the signature of the letter is acknowledged. This is perfect proof. Keywords: Accountability; Legalization; Notary Public; Underhand.